PREMARITAL SEXUAL PRACTICE AND ITS PREDICTING FACTORS AMONG YOUTH: Meta-Analysis - nisa, ananda fadila; -, Askuri - (Universitas Aisyah Pringsewu, 2025)
Background: The 15-24 age group, often called youth, is a time when many become sexually active, with a significant portion engaging in premarital sex. This behavior elevates the risk of STIs, HIV/AIDS, and unintended pregnancies. Hormonal changes are a significant internal factor in adolescents' engagement in premarital sexual behavior, as they regulate the transition from childhood to adulthood. Objective: To estimate the effect of age, gender, alcohol, smoking, pornography, and residence on the prevalence of premarital sexual practice among youth. Method: This meta-analysis was guided by a PICO research framework. Population: youth Intervention: 20-24 age, male, alcohol consumption, smoking, pornography, and rural. Comparison : 15-19 age, female, no alcohol consumption, no smoking, no pornography, and urban. Outcome: premarital sexual practice. The articles were obtained from several databases, including Google Scholar, PubMed, BMC, ScienceDirect, and Springer Link. Eligible studies were cross-sectional in design and published between 2014 and 2024. Data analysis was performed using the Review Manager 5.3 software. Results: Youth were influenced by premarital sexual practice in the presence of 20-24 age (aOR=3.11; 95% CI= 2.23 to 4.34; p 0.001), male (aOR=1.98; 95% CI= 1.14 to 3.43; p 0.001), smoking (aOR=2.23; 95% CI= 1.17 to 4.25; p 0.001), alcohol (aOR=2.98; 95% CI= 0.93 to 9.53; p 0.001), urban (aOR= 0.84; 95% CI= 0.57 to 1.26; p= 0.001) and pornography (aOR= 2.70; 95% CI= 1.67 to 4.36; p= 0.001). Conclusion: Premarital sexual practice among youth influenced by age, gender, smoking, alcohol consumption, residence and pornography.